The Use of Unidirectional Barbed Suture for Urethrovesical Anastomosis during Robot-Assisted Radical Prostatectomy: A Systematic Review and Meta-Analysis of Efficacy and Safety. - Huixin Li; Chunxiao Liu; Haibin Zhang; Wenfeng Xu; Jianhua Liu; Yong Chen; Tangxuan Li; Bin Li; Zhenquan Wu; Taolin Xia (PLoS ONE, 2015)
Background Unidirectional barbed suture (UBS) has been widely used for surgery in recent years, especially for urethrovesical anastomosis (UVA) during robot-assisted radical prostatectomy (RARP). However, the efficacy and safety comparing it with conventional non-barbed suture (CS) for UVA is still controversial. Aims The objective of this study is to assess the current evidence regarding the efficacy and safety of UBS compared with CS for UVA during RARP. Methods We comprehensively searched PubMed, Embase, The Cochrane Library, SinoMed (Chinese) and other databases on Oct. 9, 2014 to conduct a systematic review and meta-analysis of all randomized controlled trials (RCTs) and other comparative studies evaluating these two types of suture. The outcome measures included anastomosis time operative time, posterior reconstruction (PR) time, postoperative leakage (PL) rate and continence rates at different time points (4-6 weeks, 3 months, 6-12 months) after surgery. Secondary outcomes included estimated blood loss (EBL) and length of catheterization (LOC). Results Three RCTs and six observational studies including 786 cases were identified. Meta-analysis of extractable data showed that use of UBS could significantly reduce anastomosis time (weighted mean difference [WMD]:-3.98min; 95% confidence interval [CI], -6.02 -1.95; p = 0.0001), operative time (WMD:-10.06min; 95% CI, -15.45--4.67; p = 0.0003) and PR time (WMD:-0.93min; 95% CI, -1.52--0.34; p = 0.002). No significant difference was found in PL rate, EBL, LOC, or continence rates at 4-6 weeks, 3 months and 6-12 months after surgery. Conclusions Our meta-analysis indicates that UBS appears to be safe and efficient as CS for UVA during RARP with not only shorter anastomosis time, operative time, PR time, but also equivalent PL rate, EBL, LOC, and continence rates at 4-6 weeks, 3 months and 6-12 months after surgery. For the inherent limitations of the eligible studies, future more persuasive RCTs are needed to confirm and update our findings.